2018
DOI: 10.3390/ijms19113528
|View full text |Cite
|
Sign up to set email alerts
|

The Two-Faced Cytokine IL-6 in Host Defense and Diseases

Abstract: Interleukein-6 (IL-6), is produced locally from infectious or injured lesions and is delivered to the whole body via the blood stream, promptly activating the host defense system to perform diverse functions. However, excessive or sustained production of IL-6 is involved in various diseases. In diseases, the IL-6 inhibitory strategy begins with the development of the anti-IL-6 receptor antibody, tocilizumab (TCZ). This antibody has shown remarkable effects on Castleman disease, rheumatoid arthritis and juvenil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(145 citation statements)
references
References 208 publications
(217 reference statements)
5
129
0
4
Order By: Relevance
“…Up-regulated expression of IL-6 is found in PPA models [1][39] . It is reported that IL-6 can differentiates naïve CD4 + αβT cells into Th17 cells contributed to the pathophysiologic process of immune disorders [40] . IL-12 is produced by activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Up-regulated expression of IL-6 is found in PPA models [1][39] . It is reported that IL-6 can differentiates naïve CD4 + αβT cells into Th17 cells contributed to the pathophysiologic process of immune disorders [40] . IL-12 is produced by activated macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…All these findings together with basic research on the molecular properties of IL-6 family cytokines, their receptor complexes, their physiological roles, and animal-model experiments for autoimmune diseases have paved the way to developing therapeutic methods utilizing inhibitors and antibodies against cytokines. The clinical use of a humanized anti-IL-6Ra monoclonal antibody, tocilizumab, has been applied worldwide for the treatment of various inflammatory diseases, including RA (Narazaki and Kishimoto, 2018). Table 2 summarizes approved or developing inhibitors of IL-6 family cytokines and their receptors.…”
Section: Clinical Insightsmentioning
confidence: 99%
“…In relation to their clinical application, IL-6 has been well characterized as a major player in chronic inflammation, which is critical for the development of autoimmune diseases, such as rheumatoid arthritis (RA) (Hirano, 2010). Indeed, IL-6 inhibitors, including antibodies against IL-6 receptor alpha chain (IL-6Ra) or IL-6 itself, are effective treatments for various inflammatory diseases, such as RA and Castleman's disease (Boyce et al, 2018;Fajgenbaum, 2018;Narazaki and Kishimoto, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, elevated IL-6 during influenza infection has been associated with haemophagocytic syndrome resulting increased lung damage and worse outcome (21). In short, IL-6 levels vary widely depending on the type, severity and location of disease, and may result in either protection from or exacerbation of disease (11,22).…”
Section: Introductionmentioning
confidence: 99%